(untitled) - McNeill, Daniel (New York, 1993)
"Fuzzy logic" is a way to program computers so that they can mimic the imprecise way that humans make decisions. This important book traces the dramatic story of Lofti Zadeh, the Iranian-American professor who developed this concept, and his struggle to sell it to the American academic and business communities.
Keywords: Automatic control,Fuzzy systems,Computer industry,Technology transfer,Competition, International; United states,United states